Optimalisasi Dana Desa BUMDes untuk Pengelolaan Ekowisata di Desa Nglanggeran, Kabupaten Gunungkidul - Fakultas Hukum Universitas Negeri Surabaya; Zerry Akbar Yudisetyo; Irfa Ronaboyd; Elisabeth Septin Puspoayu (Fakultas Hukum, Universitas Negeri Surabaya, 2025)
For Nglanggeran Village, becoming an international tourist destination presents economic opportunities as well as challenges, including cultural commodification, environmental degradation, and erosion of local identity. This study aims to enhance the community's understanding of ecotourism management by optimizing the use of Village-Owned Enterprise (BUMDes) funds. Methods employed include socialization activities, participatory workshops, and pre- and post-test evaluations to assess knowledge improvement. The results demonstrate a substantial increase in local awareness of the sustainable utilization of Bumdes funds for tourism development. To this end, it is recommended that continuous mentoring, periodic monitoring, and legal literacy initiatives be implemented to ensure transparent, accountable, and sustainable management of eco-tourism in Nglanggeran